Pelatihan Deteksi Dini Stunting pada Balita Menggunakan Web-Based Screening Tools Bagi Kader dan Tenaga Kesehatan - Dian Isti Angraini; Anisa Nuraisa Jausal; Wiwi Febriani; Rangga Firdaus; Novita Carolia (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Stunting is a condition of chronic malnutrition. Efforts to prevent stunting involve many parties, besides government, community participation is also needed, including health workers and health cadres in assessing child growth, development and preventing stunting. The purpose is to train health workers and health cadres to conduct growth, development assessments, early detection of toddlers stunting using web-based screening tools, and to improve nutritional knowledge of toddler mothers. The method used is training in early detection of stunting in using web-based screening tools with the address